Step-by-step explanation:
By Law of Indices, a^m * a^n = a^(m+n).
Therefore 8³ * 8⁵ = 8^(3+5) = 8⁸.
Answer:
![\large\boxed{x=\dfrac{\pi}{6}\ \vee\ x=\dfrac{5\pi}{6}}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7Bx%3D%5Cdfrac%7B%5Cpi%7D%7B6%7D%5C%20%5Cvee%5C%20x%3D%5Cdfrac%7B5%5Cpi%7D%7B6%7D%7D)
Step-by-step explanation:
![4\sin^2x-4\sin x+1=0\\\\2^2\sin^2x-2(2\sin x)(1)+1^2=0\\\\(2\sin x)^2-2(2\sin x)(1)+1^2=0\qquad\text{use}\ (a-b)^2=a^2-2ab+b^2\\\\(2\sin x-1)^2=0\iff2\ain x-1=0\qquad\text{add 1 to both sides}\\\\2\sin x=1\qquad\text{divide both sides by 2}\\\\\sin x=\dfrac{1}{2}\to x=\dfrac{\pi}{6}\ \vee\ x=\dfrac{5\pi}{6}](https://tex.z-dn.net/?f=4%5Csin%5E2x-4%5Csin%20x%2B1%3D0%5C%5C%5C%5C2%5E2%5Csin%5E2x-2%282%5Csin%20x%29%281%29%2B1%5E2%3D0%5C%5C%5C%5C%282%5Csin%20x%29%5E2-2%282%5Csin%20x%29%281%29%2B1%5E2%3D0%5Cqquad%5Ctext%7Buse%7D%5C%20%28a-b%29%5E2%3Da%5E2-2ab%2Bb%5E2%5C%5C%5C%5C%282%5Csin%20x-1%29%5E2%3D0%5Ciff2%5Cain%20x-1%3D0%5Cqquad%5Ctext%7Badd%201%20to%20both%20sides%7D%5C%5C%5C%5C2%5Csin%20x%3D1%5Cqquad%5Ctext%7Bdivide%20both%20sides%20by%202%7D%5C%5C%5C%5C%5Csin%20x%3D%5Cdfrac%7B1%7D%7B2%7D%5Cto%20x%3D%5Cdfrac%7B%5Cpi%7D%7B6%7D%5C%20%5Cvee%5C%20x%3D%5Cdfrac%7B5%5Cpi%7D%7B6%7D)
Answer:
Call the numbers a, b, c, d. What does it say if their mean is 15? That would be that added together then divided by 4 you get 15. So the number before you divided by 4, which is the sum, was 60. If you know some algebra, the equation (a+b+c+d)/4=15 gives the sum of 60 when you multiply both sides
1. The slope of the ramp is √145
2. The pitch of the roof is √10
3. The grade is the road is √ 10064
Answer:
well, am confidnet that it is 4
Step-by-step explanation: